النظام المحاسبي الملائم لتطبيق نظام الإدارة بالأهداف مع دراسة تطبيقية على الشركة العربية "تاميكو" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
لقد أقرت الحكومة بتاريخ 17-1 – 1999 م تطبيق نظام الإدارة بالأهداف على عينة من شركات القطاع العام الصناعي كمدخل لإجراء إصلاحات إدارية واقتصادية جوهرية في إطار المشهد القائم على التعددية الإقتصادية وكان من ضمن هذه الشركات العربية "تاميكو". يلخص هذا البحث مفهوم نظام الإدارة بالأهداف ومتطلبات تطبيقه في الشركات ويتناول المقومات الأساسية للنظام المحاسبي الملائم لتطبيق نظام الإدارة بالأهداف وتوفير شروط نجاحه. كما يتناول واقع تطبيق نظام الإدارة بالأهداف في الشركة الطبية العربية "تاميكو" والنتائج الناجمة عن هذا التطبيق. وفي نهاية البحث نقدم بعض المقترحات لتفعيل وظائف نظام الإدارة بالأهداف وتحقيق أهدافه.     On 17 January 1999, the Syrian government decided to apply system of goals-driven management to a sample of industrial sector companies, opening the way for essential corrective administrative and economic procedures within its current policy, which is based on economic pluralism. The Arabic Medical Company, better known as TAMICO, was one of such companies. This study explains in brief the concept of goals-driven-management system and the requirements for its application by companies. It, moreover, deals with the basic components of the accountancy system appropriate for goals-driven management system and ensuring its success. Furthermore, the study examines the real application of goals-driven-management system by TAMICO and the results of that application. Finally, the study puts forward some suggestions to energize the functions of goals-driven-management system and realize its aims.